Secure cooperative event-triggered control of linear multiagent systems under DoS attacks - Feng, Zhi (2022)
This paper studies secure cooperative event-triggered control of linear multiagent systems under denial-of-service (DoS) attacks. The DoS attacks refer to interruptions of communication channels carried out by an intelligent adversary. We consider a class of time-sequence-based DoS attacks allowed to occur aperiodically. Then, an explicit analysis of the frequency and duration of DoS attacks is investigated for both secure leaderless and leader-following consensus problems. A resilient cooperative event-triggered control scheme is developed and scheduling of controller updating times is determined in the presence of DoS attacks. It is shown that based on the proposed distributed algorithms, all the agents can achieve secure consensus exponentially. The effectiveness of the developed methods is illustrated through three case studies: 1) multiple robot coordination; 2) distributed voltage regulation of power networks; and 3) distributed cooperative control of unstable dynamic systems.